2007
DOI: 10.4161/cc.6.2.3742
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification of c-MYC-Associated Proteins Using a Combined TAP/MudPIT Approach

Abstract: The c-MYC oncogene encodes a transcription factor, which is sufficient and necessary for the induction of cellular proliferation. However, the c-MYC protein is a relatively weak transactivator suggesting that it may have other functions. To identify protein interactors which may reveal new functions or represent regulators of c-MYC we systematically identified proteins associated with c-MYC in vivo using a proteomic approach. We combined tandem affinity purification (TAP) with the mass spectral multidimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 40 publications
7
117
0
2
Order By: Relevance
“…It has been shown recently that the F-box E3 ubiquitin ligase FBW8 (also known as FBXW8 or FBX29) interacts with c-MYC via both the MBII motif and the CT region and regulates c-MYC protein levels and transactivation. 44 Deletion of both these domains of c-MYC did not impair its degradation induced by UV (Fig. 3B), ruling out a role for FBW8, and by the same way of SKP2, in this phenomenon.…”
Section: Resultsmentioning
confidence: 84%
“…It has been shown recently that the F-box E3 ubiquitin ligase FBW8 (also known as FBXW8 or FBX29) interacts with c-MYC via both the MBII motif and the CT region and regulates c-MYC protein levels and transactivation. 44 Deletion of both these domains of c-MYC did not impair its degradation induced by UV (Fig. 3B), ruling out a role for FBW8, and by the same way of SKP2, in this phenomenon.…”
Section: Resultsmentioning
confidence: 84%
“…The protein mix was digested with trypsin, and the resulting peptides were separated and identified using mass spectrometry-based Mud-PIT (47,48). This resulted in the identification of known Chk1 interactors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The idea that MYC interferes with gene products that mediate DNA break repair was proposed by Karlsson et al after their observation of severe magnitude increases in chromosome breaks in normal human foreskin fibroblasts through DSB assays (Karlsson et al 2003). It was later determined by tandem affinity purification with mass spectral multidimensional protein identification technology proteomics that MYC regulates nonhomologous end-joining (NHEJ) factors (Koch et al 2007), and a recent investigation concluded that MYC directly suppresses the NHEJ pathway causing inhibition of DSB repair and V(D)J recombination through inhibitory MYC box II binding with Ku70 in vitro and in vivo (Li et al 2012). It has also been reported that MYC inhibits homologous recombination through regulation of RAD51 in various cancer cell lines (Luoto et al 2010).…”
Section: Myc and Replication Stressmentioning
confidence: 99%